2003
DOI: 10.4049/jimmunol.170.4.1870
|View full text |Cite
|
Sign up to set email alerts
|

Stat Signals Release Activated Naive Th Cells from an Anergic Checkpoint

Abstract: Activation of naive Th lymphocytes by the TCR and the costimulatory molecule, CD28, is believed to provide competent signals for differentiation to effector cells. Such activated cells proliferated and expressed IL-2, but arrested in an immature state maintained by CTLA-4. Although unresponsive to restimulation by TCR/CD28 alone, restimulation with TCR/CD28 and either Stat4- or Stat6-mediated cytokine signals rescued cells to proliferate and differentiate to the appropriately matched canonical Th subsets. Addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 61 publications
2
14
0
Order By: Relevance
“…Prior studies have shown that in vitro, in the presence of Th2-polarizing conditions, STAT6KO cells cease dividing after 3 days and display a phenotype of incomplete activation (14). The same study shows that under Th1-polarizing conditions, STAT4KO cells are incompletely activated.…”
Section: Discussionsupporting
confidence: 56%
“…Prior studies have shown that in vitro, in the presence of Th2-polarizing conditions, STAT6KO cells cease dividing after 3 days and display a phenotype of incomplete activation (14). The same study shows that under Th1-polarizing conditions, STAT4KO cells are incompletely activated.…”
Section: Discussionsupporting
confidence: 56%
“…Interestingly, a strong association exists between TCR ligation and expression of CIS, a negative modulator of STAT5 activity (29). Moreover, the simultaneous activation of STAT in conjunction with TCR-mediated signaling is able to allow progression of cell division and release of anergy (30). A recent study proposed a role for STAT5 in differentiation and maintenance of the IFN-␥ secreting Th1 phenotype (31).…”
Section: Discussionmentioning
confidence: 99%
“…CTLA4 is induced following T-cell receptor (TCR)/CD28 stimulation; it arrests activated Tcells, thereby keeping them in an anergic state. Arrested T-cells exit the lymph nodes and enter the circulation [19]. Blocking CTLA4 can intensify T-cell responses and exacerbate autoimmune disease [20]; CTLA4-deficient mice die by 3-4 weeks of age due to multi-organ lymphocytic infiltration and tissue destruction [17].…”
mentioning
confidence: 99%